A Mindfulness-Based Stress Reduction (MBSR) dalam mengurangi Academic Anxiety pada Mahasiswa - syafii, Hisyam; Purnomo , Halim; Azhari, Husain (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2024)
This study examines the effectiveness of Mindfulness-Based Stress Reduction (MBSR) in reducing academic anxiety among students at Muhammadiyah and Aisyiah Universities (PTMA) through a systematic literature review. Academic anxiety can affect students' performance and well-being. The method used was a systematic literature review by searching for relevant research articles from electronic databases such as Google Scholar, PubMed, and ERIC. Inclusion criteria included studies on MBSR, academic anxiety, and Islamic higher education settings, specifically PTMA. The results of the review showed that the majority of studies reported a significant reduction in academic anxiety levels after MBSR intervention. Some studies also showed improvements in academic performance and psychological well-being. However, variations in methodology and research contexts suggest the need for further research in the PTMA setting. In conclusion, MBSR has influence as an effective intervention to reduce academic anxiety among PTMA students, although further research is needed to confirm these findings in the specific context of PTMA.